Integrative Curriculum Framework Shapes Secondary Aqidah Akhlaq Assessment And Planning: Kerangka Kurikulum Integratif Membentuk Perencanaan Dan Penilaian Aqidah Akhlaq Menengah - Bilal Abdullah; Fadrianti Fadrianti (Halaqa: Islamic Education Journal, 2026)
General Background Contemporary Islamic education struggles to balance academic achievement with students' moral and spiritual development, frequently resulting in disjointed learning outcomes. Specific Background Instructional practices in Aqidah-Akhlaq primarily emphasize normative and cognitive dimensions while neglecting crucial affective and spiritual character cultivation. Knowledge Gap A comprehensive pedagogical structure connecting spiritual awareness, ethical behavior, and reflective practice remains notably absent from current conventional teaching models. Aims This study develops a comprehensive planning and evaluation framework utilizing an integrative curriculum model grounded in love-based pedagogy for secondary education. Results The proposed conceptual model merges teaching design, transformative learning practices, and authentic assessment to holistically evaluate cognitive, spiritual, moral, and behavioral achievements through reflection, observation, portfolios, and socio-religious practices. Novelty Placing love as the fundamental epistemological and pedagogical principle uniquely strengthens meaningful teacher-student relationships while seamlessly unifying learners' cognitive, emotional, and behavioral dimensions. Implications This model transitions Islamic education toward a humanistic and transformative paradigm, though subsequent empirical validation through pilot implementation and instrument testing across diverse educational contexts remains necessary. Highlights Love pedagogy connects faith, morality, and reflective actions. Authentic measurement methods examine students' spiritual and behavioral development. Humanistic teaching approaches build meaningful relationships between teachers and learners. Keywords Love Based Pedagogy; Holistic Evaluation; Islamic Education; Authentic Measurement; Character Development